Designing redder and brighter fluorophores by synergistic tuning of ground and excited states. Issue 17 (11th February 2019) - Chen, Cheng; Baranov, Mikhail S.; Zhu, Liangdong; Baleeva, Nadezhda S.; Smirnov, Alexander Yu.; Zaitseva, Snizhana O.; Yampolsky, Ilia V.; Solntsev, Kyril M.; Fang, Chong
Abstract : We devise a unique "double-donor–one-acceptor" strategy to effectively tune the "dark" GFP-core outside protein matrix into redder and brighter fluorophores. Abstract : We strategically modified the GFP core via chemical synthesis to make redder and brighter biomimetic fluorophores. Based on quantum calculations, solvatochromism analysis, and femtosecond Raman, we unveiled the additive effect of tuning the electronic ground and excited states, respectively, to achieve a dramatic emission redshift with a "double-donor–one-acceptor" structure.